FDI versus Exports Substitutes or Complements? A Three Nations Model and Empirical Evidence - Harald Oberhofer; Michael Pfaffermayr (FIW - Research Centre International Economics, 2008)
There are two main options for companies to serve foreign markets; exports and foreign direct investment (FDI). Based on the Helpman, Melitz and Yeaple (2004) model for two host countries this paper derives a clear theoretical prediction for the decision between both strategies. A bivariate probit model is estimated using AMADEUS database to analyse the probability of using one or the other strategy. The empirical evidence indicates that a considerable number of companies use a combination of both strategies to serve foreign markets, which is in line with the analyzed three country model.
Keywords: C35; D21; F12; 330; Exports; Foreing Direct Investment; Three Nations Model; Bivariate Probit Estimation